Advancing Stem Cell Therapy for Repair of Damaged Lung Microvasculature in Amyotrophic Lateral Sclerosis. (23rd March 2020) - Garbuzova-Davis, Svitlana; Shell, Robert; Mustafa, Hilmi; Hailu, Surafuale; Willing, Alison E.; Sanberg, Paul R.; Borlongan, Cesario V.
Amyotrophic lateral sclerosis (ALS) is a fatal disease of motor neuron degeneration in the brain and spinal cord. Progressive paralysis of the diaphragm and other respiratory muscles leading to respiratory dysfunction and failure is the most common cause of death in ALS patients. Respiratory impairment has also been shown in animal models of ALS. Vascular pathology is another recently recognized hallmark of ALS pathogenesis. Central nervous system (CNS) capillary damage is a shared disease element in ALS rodent models and ALS patients. Microvascular impairment outside of the CNS, such as in the lungs, may occur in ALS, triggering lung damage and affecting breathing function. Stem cell therapy is a promising treatment for ALS. However, this therapeutic strategy has primarily targeted rescue of degenerated motor neurons. We showed functional benefits from intravenous delivery of human bone marrow (hBM) stem cells on restoration of capillary integrity in the CNS of an superoxide dismutase 1 (SOD1) mouse model of ALS. Due to the widespread distribution of transplanted cells via this route, administered cells may enter the lungs and effectively restore microvasculature in this respiratory organ. Here, we provided preliminary evidence of the potential role of microvasculature dysfunction in prompting lung damage and treatment approaches for repair of respiratory function in ALS. Our initial studies showed proof-of-principle that microvascular damage in ALS mice results in lung petechiae at the late stage of disease and that systemic transplantation of mainly hBM-derived endothelial progenitor cells shows potential to promote lung restoration via re-established vascular integrity. Our new understanding of previously underexplored lung competence in this disease may facilitate therapy targeting restoration of respiratory function in ALS.